ANALISIS USER EXPERIENCE PADA WEBSITE MIND & SOUL MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Hosea, Wilson Gabriel; Rahman, Syaiful; Arianti (KHARISMA Tech, 2023)
Abstract: This study aims to analyze User Experience on the Mind &; Soul website based on user respondents using the System Usability Scale method. This research began by distributing a questionnaire containing 10 statements that had been prepared by the Usability Scale System to users of the Mind &Soul website as a data collection medium, then continued by processing the questionnaire result data. Data collection is carried out by distributing questionnaires with respondents. Data processing was carried out using the System Usability Scale method to get results, namely a score of 68.4 declared Imarginal High and entered into grade D with an OK rating. Website Mind &; Soul can be concluded that the Website is worth using. Website Mind & Soul can be concluded that the Website is suitable for use by users who need an online consultation place.